Trait‐driven responses of grassland butterflies to habitat quality and matrix composition in mosaic agricultural landscapes. Issue 1 (25th October 2016) - van Halder, Inge; Thierry, Mélanie; Villemey, Anne; Ouin, Annie; Archaux, Frédéric; Barbaro, Luc; Balent, Gérard; Benot, Marie‐Lise
Abstract: The relative importance of local‐ and landscape‐scale factors on butterfly diversity can depend on the quality, management intensity and landscape context of habitat patches. This study aims to disentangle these local and landscape effects on taxonomic and functional composition of butterfly communities within mosaic agricultural landscapes. We sampled butterflies in 144 grasslands and 142 linear elements (road verges and herbaceous strips between crops) in three regions in France. We analysed how local and landscape variables affected butterfly species richness, community composition and community‐weighted mean traits. Local habitat variables explained more variation in butterfly richness and community composition than landscape‐scale variables, both in grasslands and linear elements. Floristic composition was the most important predictor of butterfly community composition. In sites with tall vegetation and low biomass removal, butterfly communities were more dominated by species with long larval development, low fecundity and low mobility. Landscape variables were proportionally more influential in linear elements than in grasslands. Increasing landscape heterogeneity, by favouring agricultural mosaics with semi‐natural grasslands and woodlands, appeared to be beneficial for butterflies, especially for specialist species. Agri‐environmental schemes aiming at preserving butterfly diversity should thus primarily provide incentives to conserve or restore grasslands with low management intensity, while promoting at the same time landscape heterogeneity.